Factors affecting SPF in vitro measurement and correlation with in vivo results. (8th December 2016) - Dimitrovska Cvetkovska, A.; Manfredini, S.; Ziosi, P.; Molesini, S.; Dissette, V.; Magri, I.; Scapoli, C.; Carrieri, A.; Durini, E.; Vertuani, S.
Abstract: Objective: The in vitro evaluation of SPF is still a problem due to the lack of repeatability and correlation between the in vitro and in vivo data, and many authors are currently working to develop an internationally harmonized method. Very recently, the use of several "adjuvant" ingredients such as boosters, antioxidants, immunomodulators, solvents and film‐forming ingredients have further complicated the pattern for product developers that should frequently run in vivo test. The aim of this study was to understand whether a simple and cheap in vitro method could be optimized in order to provide both statistically repeatable and predictive SPF measurement. Methods: In vitro SPF assessments were carried out on 75 commercial products. The SPF was measured according to two laboratory methods (A and B), using different substrates (PMMA and surgical tape Transpore™), quantity of product and spectrophotometers. In order to evaluate whether a standard technique of spreading could lead to a statistically reliable result, we applied different spreading pressure (100 g and 200 g). Furthermore, we investigate whether other parameters characterizing the product (SPF category, filter and texture) might represent statically significant variables affecting the measures. We then compared the results obtained from in vitro SPF measure of 11 products to in vivo SPF, in order to assess the predictability of in vitro methods. Results: Several problems were encountered in confirming the weakness of the in vitro procedures. Pressure, SPF category, filter and texture did not affect significantly the results. Overall best results were obtained with the B2 method that in terms of repeatability and predictivity provided statistically better results. Method A with Transpore™ tape showed better in vitro – in vivo correlation than Method B with PMMA plates. Conclusion: In our investigation, we demonstrated that it is possible for a single laboratory to optimize internal methods and protocols to achieve repeatable and predictive in vitro results, but it is extremely difficult to develop methods reproducible and equally reliable in different laboratories, probably due to "external variables" (e.g. environmental, operator), which are difficult to control.